Water Pollution and Cyanobacteria's Variation of Rivers Surrounding Southern Taihu Lake, China. (1st May 2013) - Sun, Mingyang; Huang, Linglin; Tan, Lisha; Yang, Zhe; Baig, Shams Ali; Sheng, Tiantian; Zhu, Hong; Xu, Xinhua
Abstract : The water quality and cyanobacterial variation of rivers surrounding southern Taihu Lake, China were purposively monitored from 2008 to 2010. Trophic level index (TLI) was used to evaluate the trophic levels of southern Taihu Lake. Results showed a considerable decline in the monitored data compared with 2007, and the data showed downward trends year after year. The TLI decreased from 55.6 to 51.3, which implied that southern Taihu Lake was mildly eutrophic. The water quality and cyanobacterial variation indicated a positive response to the adopted control measures in the southern Taihu Lake basin, but the intra‐ and inter‐annual variability was still quite varied. High concentrations of nitrogen and phosphorus typically lead to algae outbreaks, however, the cyanobacteria growth may result in a decline of the concentration of nitrogen and phosphorus. Temperature and other weather conditions are also important factors for algae outbreaks; the risk of blue‐green algal blooms still persists.